2019
DOI: 10.1073/pnas.1909883116
|View full text |Cite
|
Sign up to set email alerts
|

Circadian lipid synthesis in brown fat maintains murine body temperature during chronic cold

Abstract: Ambient temperature influences the molecular clock and lipid metabolism, but the impact of chronic cold exposure on circadian lipid metabolism in thermogenic brown adipose tissue (BAT) has not been studied. Here we show that during chronic cold exposure (1 wk at 4 °C), genes controlling de novo lipogenesis (DNL) includingSrebp1, the master transcriptional regulator of DNL, acquired high-amplitude circadian rhythms in thermogenic BAT. These conditions activated mechanistic target of rapamycin 1 (mTORC1), an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 58 publications
6
41
0
Order By: Relevance
“…One cause for the lower liver lipids in fasted EODF animals could be the increased energy expenditure from WAT browning seen previously (Li et al, 2017). However, given our liver EODF-induced protein changes of a increased DNL enzymes and fatty acid oxidation enzymes regardless of harvest state, these animals may have coupled the pathway of DNL with fatty acid oxidation to generate a futile energy-consuming cycle (Solinas et al 2015), similar to that of brown adipose tissue (Adlanmerini et al, 2019). This could also contribute to the elevated body temperature of EODF mice seen previously (Li et al, 2017), as the liver can participate in non-shivering thermogenesis (Stoner, 1973).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…One cause for the lower liver lipids in fasted EODF animals could be the increased energy expenditure from WAT browning seen previously (Li et al, 2017). However, given our liver EODF-induced protein changes of a increased DNL enzymes and fatty acid oxidation enzymes regardless of harvest state, these animals may have coupled the pathway of DNL with fatty acid oxidation to generate a futile energy-consuming cycle (Solinas et al 2015), similar to that of brown adipose tissue (Adlanmerini et al, 2019). This could also contribute to the elevated body temperature of EODF mice seen previously (Li et al, 2017), as the liver can participate in non-shivering thermogenesis (Stoner, 1973).…”
Section: Discussionmentioning
confidence: 91%
“…Likewise, liver-specific FASN mutants display detrimental phenotypes compared to wild-type animals, including greatly increased steatosis after fasting (Chakravarthy et al, 2005). Furthermore, two recent studies have shown that DNL is needed for fasting-induced fatty acid oxidation in brown adipose tissue (Adlanmerini et al, 2019;Sanchez-Gurmaches et al, 2018). These studies show that DNL may be directly coupled to fatty acid oxidation under certain circumstances to generate a futile cycle that wastes energy as heat.…”
Section: Discussionmentioning
confidence: 99%
“…We first determined the diurnal expression of REV-ERBa in non-SCN hypothalamic nuclei of mice with epitopetagged endogenous REV-ERBa (HA-REV-ERBa mice, previously described 23 ) to specifically visualize the protein by immunofluorescence. Peak expression was observed between zeitgeber time (ZT) 1-7 ( Figure 1A), and thus studies of REV-ERBs function in hypothalamus were conducted at ZT 1-4.…”
Section: Specific Deletion Of Rev-erba and B In Non-scn Hypothalamic mentioning
confidence: 99%
“…To delineate hypothalamic-specific functions of REV-ERBs, mice homozygous for floxed alleles of REV-ERBa and REV-ERBb 23,24 were crossed to Nkx2.1-Cre mice, which express Cre in the ventromedial tuberal hypothalamic nuclei but, importantly, not in the SCN 25 . This Cre driver is also expressed in the lung and thyroid gland but not in any other peripheral metabolic organs 25,26 .…”
Section: Specific Deletion Of Rev-erba and B In Non-scn Hypothalamic mentioning
confidence: 99%
See 1 more Smart Citation